Effects of dietary lysine and methionine supplementation on growth, nutrient utilization and carcass compositions in beluga, Huso huso, fed soy protein-based diet - Mohseni, M.; Pourkazemi, M.; Seyed Hassani, M.H.; Pourali, H.R. (2016)
A feeding trial was conducted to examine the effects of dietary supplementation of lysine and methionine on growth, nutrient utilization and carcass compositions in beluga, Huso huso. Four experimental soy protein based diets D0 (without lysine or methionine supplementation), D1 (lysine supplementation alone), D2 (methionine supplementation alone) and D3 (both lysine and methionine supplementation) were fed to triplicate groups. 240 fish with an average weight of 144.6 ± 4.64 g were fed the experimental diets for 12wk. L-Lysine and DL-methionine were added to the diets containing 344 g kg-1 soybean meals at 22.02 and 12.94 g kg-1 of dry diet respectively. Significant higher weight gain, specific growth rate, protein efficiency ratio, condition factor, feed efficiency ratio, whole muscle protein and protein apparent digestibility were observed in fish fed soya protein-based diet supplemented with both lysine and methionine than that of fish of other dietary groups. There were no significant differences among fish fed diet supplemented with either methionine or lysine. Growth performances, feed utilization, carcass composition and apparent digestibility coefficients of protein, lipid and dry matter of fish fed control diet was significantly lower than those of fish fed diet supplemented both lysine and methionine and supplemented with either methionine or lysine. It can be concluded that beluga, fingerlings effectively utilize the supplemental amino acids (L-Lysine at 22.02 g kg-1 dry diet and DL-methionine at 12.94 g kg-1 dry diet) in the diets containing 344 g kg-1 soybean meals for better carcass proximate compositions, growth performance and feed efficiency and utilization.